Characterization of Soluble Glandless Cottonseed Meal Proteins Based on Electrophoresis, Functional Properties, and Microscopic Structure. Issue 10 (13th September 2019) - Delgado, Efren; Valverde‐Quiroz, Luisa; Lopez, Denisse; Cooke, Peter; Valles‐Rosales, Delia; Flores, Nancy
Abstract : Abstract: This investigation aimed to extract and characterize the GCSM proteins, determine their solubility potential at two different temperatures and different solvents, and explore their functional properties. During the extraction, no water‐ or ethanol‐soluble protein was found. Most of the protein was extracted with KOH solution. GCSM showed major protein bands between 13, 273 and 56, 564 Da with an isoelectric point of 5.1. The results showed that extraction temperature and solvent affected the amount of protein extracted from GCSM. The highest protein yield (63.4%) was obtained with KOH at 55 °C. Fat content negatively affected the protein solubility. The highest protein purity (99.9%) was obtained with 6% of fat content and the lowest one with 19% of fat content. GCSM has a high glutamic acid content, followed by arginine and aspartic acid compared to the other amino acids. The essential amino acids make up about 30.0% of the total amino acid concentration in KOH‐soluble fractions. The results showed a denaturation temperature of GCSM protein ranging from 61.4 to 63.6 °C. Scanning electron microscopy reveals a microglobular protein structure. GCSM protein isolate showed lower ( P < 0.05) water‐holding and oil‐holding capacity but similar gelation properties as soy protein. GCSM protein shows a high foaming capacity at high pH values and high emulsion stability. Practical Application: The results of this investigation have a direct impact on the plant protein processing industry. This paper presents a new source of plant protein with a high foaming capacity in alkaline conditions with potential applications for human consumption and feed for aquaculture and animals. The results of this research may impact the cotton producers who can increase their income, and the aquaculture industry will have a cheaper source of protein that can partially substitute the expensive fishmeal. Cottonseed protein can be used to develop high protein extruded snacks and other functional foods, such as plant protein‐based food products.